Education for Making complementary food Biscuits for breast milk for Mothers Who Have Toddlers Age 6-24 Months And Posyandu Cadres - Nelly Mariati; Wulandari Wulandari; Mirawati Mirawati (Comment: an International Journal of Community Development, 2021)
Complementary food for breast milk (MP-ASI) is food or drink that contains nutrients and is given to infants or children aged 6-24 months to meet nutritional needs other than breast milk. Efforts to improve community nutrition can be done by increasing food consumption through a food diversification approach. MP-ASI baby biscuits are usually made from wheat flour or rice flour. This does not support food diversification so that other additives are needed. The purpose of this activity is that participants are expected to understand how to process MP-ASI biscuits for toddlers. The method of implementing community service used is in the form of counseling with lectures and discussions as well as demonstrations in making MP-ASI biscuits. After the implementation of this community service activity, conclusions that can be drawn include an increase in the knowledge and skills of mothers who have toddlers in processing nutritious MP-ASI biscuits. The hope is that the processing of MP-ASI such as biscuits that are safe and healthy continues to be carried out so that the nutrition of toddlers is fulfilled.